INFLUENCE OF GREEN MARKETING STRATEGIES ON CONSUMERS’ SUSTAINABLE CONSUMPTION BEHAVIOR: IMPLICATIONS FOR RESTAURANT’S SALES USING SOCIAL MEDIA MARKETING STRATEGIES - 1. Ms. Muskan Sharma, 2. Prof. (Dr) Broto Bhardwaj (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Purpose of this research paper is to study the influence of the social media marketing strategies including the green strategies on restaurant sales and growth. The methodology includes the mixed method in which empirical analysis was used and implications were drawn. Findings suggests that the ambiance, context, music, food quality and outlet outlay influences the restaurant sales significantly. Apart from that, if the restaurants are using green strategies, that also influences how the consumers perceives the influence of carbon foot print and allows the customer to make decisions about purchase. This is because after Covid 19, the consumers have become very conscious about the green strategies which can actually help the sustainable businesses. Implications include the role of businesses in creating green people, planet profit collaboration for sustainable green businesses (3P model for sustainable and SDG).